Liposomal Phenylephrine Nanoparticles Enhance the Antitumor Activity of Intratumoral Chemotherapy in a Preclinical Model of Melanoma - Gabriel, Emmanuel M.; Bahr, Deborah; Rachamala, Hari Krishnareddy; Madamsetty, Vijay S.; Shreeder, Barath; Bagaria, Sanjay; Escobedo, Amber L.; Reid, Joel M.; Mukhopadhyay, Debabrata (ACS biomaterials science & engineering, 2024)
Intratumoral injection of anticancer agents has limited efficacy and is not routinely used for most cancers. In this study, we aimed to improve the efficacy of intratumoral chemotherapy using a novel approach comprising peri-tumoral injection of sustained-release liposomal nanoparticles containing phenylephrine, which is a potent vasoconstrictor. Using a preclinical model of melanoma, we have previously shown that systemically administered (intravenous) phenylephrine could transiently shunt blood flow to the tumor at the time of drug delivery, which in turn improved antitumor responses. This approach was called dynamic control of tumor-associated vessels. Herein, we used liposomal phenylephrine nanoparticles as a “local” dynamic control strategy for the B16 melanoma. Local dynamic control was shown to increase the retention and exposure time of tumors to intratumorally injected chemotherapy (melphalan). C57BL/6 mice bearing B16 tumors were treated with intratumoral melphalan and peri-tumoral injection of sustained-release liposomal phenylephrine nanoparticles (i.e., the local dynamic control protocol). These mice had statistically significantly improved antitumor responses compared to melphalan alone (p = 0.0011), whereby 58.3% obtained long-term complete clinical response. Our novel approach of local dynamic control demonstrated significantly enhanced antitumor efficacy and is the subject of future clinical trials being designed by our group.